Variations in raindrop size distribution and specific attenuation due to rain in Nigeria - Adimula, I.A; Ajayi, G.O (annals of telecommunications - annales des télécommunications, 2023)
International journal annales annals of telecommunications - annales des télécommunications Vol.51 No1 p.87-93